CRISPR/Cas12a-Based Biosensing: Advances in Mechanisms and Applications for Nucleic Acid Detection - Kun Du; Qinlong Zeng; Mingjun Jiang; Zhiqing Hu; Miaojin Zhou; Kun Xia (Biosensors)
Nucleic acid detection technology is crucial for molecular diagnosis. The advent of CRISPR/Cas12a-based nucleic acid detection has considerably broadened its scope, from the identification of infectious disease-causing microorganisms to the detection of disease-associated biomarkers. This innovative system capitalizes on the non-specific single-strand cleavage activity of Cas12a upon target DNA recognition. By employing a fluorescent probe in the form of a single-stranded DNA/RNA, this technology enables the observation of fluorescence changes resulting from nonspecific cleavage, thereby facilitating detection. CRISPR/Cas12a-based detection systems can be regarded as a new type of biosensor, offering a practical and efficient approach for nucleic acid analysis in various diagnostic settings. CRISPR/Cas12a-based biosensors outperform conventional nucleic acid detection methods in terms of portability, simplicity, speed, and efficiency. In this review, we elucidate the detection principle of CRISPR/Cas12a-based biosensors and their application in disease diagnostics and discuss recent innovations and technological challenges, aiming to provide insights for the research and further development of CRISPR/Cas12a-based biosensors in personalized medicine. Our findings show that although CRISPR/Cas12a-based biosensors have considerable potential for various applications and theoretical research, certain challenges remain. These include simplifying the reaction process, enhancing precision, broadening the scope of disease detection, and facilitating the translation of research findings into clinical practice. We anticipate that ongoing advancements in CRISPR/Cas12a-based biosensors will address these challenges.